Cytosolic Nuclear Sensor Dhx9 Controls Medullary Thymic Epithelial Cell Differentiation by p53-Mediated Pathways - Dong, Xue; Zhang, Jiayu; Zhang, Qian; Liang, Zhanfeng; Xu, Yanan; Zhao, Yong; Zhang, Baojun (Frontiers in Immunology, 2022)
Thymic epithelial cells (TECs) critically participate in T cell maturation and selection to establish immunity to foreign antigens and immune tolerance to self-antigens of T cells. It is well known that many intracellular and extracellular molecules elegantly have mastered the development of medullary TECs (mTECs) and cortical mTECs (cTECs). However, the role played by NTP-dependent helicase proteins in TEC development is currently unclear. Herein, we created mice with a TEC-specific DExD/H-box helicase 9 (Dhx9) deletion (Dhx9 cKO) to study the involvement of Dhx9 in TEC differentiation and function. We found that a Dhx9 deficiency in TECs caused significantly decreased cell numbers of TECs, including mTECs and thymic tuft cells, accompanied by accelerated mTECs maturation but no detectable effect on cTECs. Dhx9-deleted mTECs transcriptionally expressed poor tissue-restricted antigen profiles compared with WT mTECs. Importantly, Dhx9 cKO mice displayed an impaired thymopoiesis, poor thymic T cell output, and they suffered from spontaneous autoimmune disorders. RNA-seq analysis showed that the Dhx9 deficiency caused an upregulated DNA damage response pathway and Gadd45, Cdkn1a, Cdc25, Wee1, and Myt1 expression to induce cell cycle arrest in mTECs. In contrast, the p53-dependent upregulated RANK-NF-κB pathway axis accelerated the maturation of mTECs. Our results collectively indicated that Dhx9, a cytosolic nuclear sensor recognizing viral DNA or RNA, played an important role in mTEC development and function in mice.